Does Gender Matter for Green Behaviour? An Empirical Investigation With Cross-Country Data From the Enterprise Surveys - Camilla Jensen (SAGE Open)
Across 8 European and Central Asian countries, the paper explores the hypothesis that female entrepreneurs are more likely to exhibit green behaviour by adopting new and more environmentally friendly and/or energy efficient technologies (ecopreneurship). Methodological rigor (such as broad sampling and measurement of institutions using latent constructs derived from factor analysis) is made possible in this study thanks to the richness of data provided by the World Banks’ Enterprise Surveys. The traditional simple linear approach to the adoption of gender variables in quantitative studies is applied. Results demonstrate that women exhibit a higher propensity to act in ecopreneurial ways. However, the most important finding of the study is that retroductively, a paradox emerges due to the meta-institutional dimension of the data (across former socialist vs. capitalist systems). The results show that as gender participation is mainstreamed, for example by subjecting female values to male institutions of professional management, behaviour is also mainstreamed. The paper concludes that for quantitative gender studies to attain more legitimacy vis-à-vis institutional theory and institutional feminism, the role of gender requires a better grounding in theories of how institutions work to produce economic outcomes.